Influence of Learning Environment and Teachers Skills On Academic Achievement Among Senior Secondary Schools Students in Jigawa State Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2023)
This study examined the Influence of learning environment, and teacher’s skill on students’ academic achievement among senior secondary school students in Jigawa State Nigeria. Using Ex-post facto design. Three objectives and three null hypotheses were formulated and tested. the population of the study consist of 28202 S.S.S. 1 students and 477 teachers out of which 381students and 217 teachers were randomly selected as sample for the study in Nine senior secondary schools in Jigawa state.Two instruments will be adapted and used in this research: Students learning environment inventory, (SLEI) and Teachers skills inventory (TSI)).All the two instruments have construct validity and reliability of  internal consistency with alpha coefficients of 0.72  for SLEI and  0.84 for TSI  respectively. While Average scores for qualifying examination in English and mathematics 2021/2022 is to be used as students’ academic achievement (SAA).PPMC and T-Test will be used for data analysis with the aid of SPSS 2006 version. Data collected for the study will be statistically analyzed using descriptive statistics of x and S.D as well as t-test for independent samples, all hypotheses will be tested at 0.05 level of significance, The Findings of the study revealed that, there is  significant differences in students’ academic achievement on the basis of conducive or un conducive learning environment among senior secondary school  students, significant  differences is  found between academic achievement of senior secondary school students taught by teachers with different teaching skills in Jigawa state Recommendations will be made at the end of the study